Descriptive Study of Diet of Elderly with Hypertensive Disease At Kepadangan Health Center - Firdausy Nurida, Bunga; Maimuna, Siti; Dari, Tanty Wulan (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Hypertension is a non-communicable disease that is often found in the community and causes high morbidity. Hypertension is a continuous increase in blood pressure so that it exceeds normal limits. Hypertension has become a global problem because of its prevalence that continues to increase from year to year. Hypertension can occur in anyone, both men and women. The risk of developing hypertension will increase at the age of 60 years and over because blood naturally tends to increase with age. This study aims to determine the descriptive study of the diet of the elderly with hypertension at the Kepadangan Health Center. This study used a descriptive method approach using questionnaires developed by researchers to determine diet. In this study using simple random sampling, each member of the population has the same opportunity to be selected as a sample according to sample criteria. The results showed that of the 40 elderly with hypertension at the Kepadangan Health Center, most were in the age category of 60-74 years, namely as many as 35 people (87.5%) out of 40 people. Diet is not the main factor causing hypertension because increasing age, especially the elderly, will experience a decrease in organ function. The number of elderly has a balanced result between the elderly with a bad diet and a good diet. Diet also determines health for the body. High blood pressure in the elderly can be caused by dietary factors.